2007
DOI: 10.1038/sj.ejhg.5201801
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol kinase deficiency alters expression of genes involved in lipid metabolism, carbohydrate metabolism, and insulin signaling

Abstract: Glycerol kinase (GK) is at the interface of fat and carbohydrate metabolism and has been implicated in insulin resistance and type 2 diabetes mellitus. To define GK's role in insulin resistance, we examined gene expression in brown adipose tissue in a glycerol kinase knockout (KO) mouse model using microarray analysis. Global gene expression profiles of KO mice were distinct from wild type with 668 differentially expressed genes. These include genes involved in lipid metabolism, carbohydrate metabolism, insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 53 publications
(40 reference statements)
2
54
0
1
Order By: Relevance
“…Gene expression of GK, G6PDH, fructose-1,6-bisphosphatase (F16bPase), pyruvate kinase (PyK), phosphoenolpyruvate carboxykinase (PEPCK), and citrate synthase (CS) was assayed by real time (RT)-PCR, as described previously [18] with 18s rRNA (Applied Biosystems, Foster City, CA) used as an endogenous control. Briefly, mRNA extracted from the cell lines was used to synthesize cDNA by using Superscript III reverse transcriptase (Invitrogen) and random primers.…”
Section: Gene Expression Assaysmentioning
confidence: 99%
“…Gene expression of GK, G6PDH, fructose-1,6-bisphosphatase (F16bPase), pyruvate kinase (PyK), phosphoenolpyruvate carboxykinase (PEPCK), and citrate synthase (CS) was assayed by real time (RT)-PCR, as described previously [18] with 18s rRNA (Applied Biosystems, Foster City, CA) used as an endogenous control. Briefly, mRNA extracted from the cell lines was used to synthesize cDNA by using Superscript III reverse transcriptase (Invitrogen) and random primers.…”
Section: Gene Expression Assaysmentioning
confidence: 99%
“…Only one patient from the literature (IVS9-1G>T) who had a history of metabolic and CNS crises at the age 6 years and 3 months, indicating the symptomatic form of GKD, but he was uneventful in the neonatal period and early childhood [10]. Previous studies showed that there was no genotype-phenotype correlation in GKD [1,11,12]. Our patient presented no symptoms, excepting no weight gain.…”
Section: Analysis Of Gk Expression By Real-time Quantitative Pcrmentioning
confidence: 55%
“…Only one patient from the literature (IVS9-1G>T) who had a history of metabolic and CNS crises at the age 6 years and 3 months, indicating the symptomatic form of GKD, but he was uneventful in the neonatal period and early childhood [10]. Figure 3: (1) Sequencing results blast of the products a and b, query is a, and the other is b; (2) Sequencing results blast of the products a and c, the above one is a, the other is c; (3) Sequencing results blast of the products b and d, the above is b, the below is d. Mei L, Tan H, Li H, Lv W, et al (2017) Previous studies showed that there was no genotype-phenotype correlation in GKD [1,11,12]. Our patient presented no symptoms, excepting no weight gain.…”
Section: Citation: Zeng L Mei L Tan H Li H Lv W Et Al (2017) a mentioning
confidence: 99%
“…24 Such sophisticated methods are required to deal adequately with environmental input while maintaining homeostasis, as well as with the complexities of eukaryotic organisms, which result from eukaryotes' multicellularity, compartmentalization of metabolites into organelles, and complex transport mechanisms. [25][26][27][28] In the liver, ASL is one of the enzymes that participates in the urea cycle. A number of studies have attempted to draw a correlation between the genotype, which determines the level of ASL enzyme activity, and the phenotype severity of patients with ASA, with limited success.…”
Section: Effects Of Metabolites On Dynamic Metabolic Fluxesmentioning
confidence: 99%